Loan Disbursement Performance Post Establishment of Ultra Micro Holding - Anggraeni, Aniesya Sefia; Ma'arif, Mohammad Syamsul; Zulbainarni, Nimmi (Ridwan Institute, 2023)
This study has several research objectives, namely (1.) identifying the determinants of UMi Holding loan distribution; (2.) analyze the financial performance consisting of the holding holding company, namely BRI, and two holding subsidiaries, namely Pegadaian and PNM. Financial performance analysis is carried out by comparing the financial performance data of each entity before holding, namely in 2013-2021 and financial data after holding, namely 2022; The results of this study show that there are total assets (company size), tangibility, liquidity, and debt to equity ratio that affect the distribution of UMi Holding loans, in addition, the financial performance of UMi Holding entities has increased, especially in BRI which has experienced a significant increase in performance. Henceforth, practical and academic recommendations are presented at the end of the study.